PENINGKATAN KEMAMPUAN LITERASI DENGAN FISHBOND DIAGRAM PADA SISWA SDS HATI KUDUS - Susanto, Ratnawati; Syofyan, Harlinda; Nurlinda, Belina Dwi; Br, Gempita Besella; Sugiharta, Rizki; Sumarni, Sumarni; Lestari, Tantri Hertika (Jurnal Pengabdian Masyarakat AbdiMas, 2019)
AbstractSDN Duri Kepa 17 Pagi and SDN Jelambar 01 Pagi have problems over pedagogic competency values that focus on the ability to understand the characteristics of the students. This is due to the absence of pedagogic pedagogy development programs for teachers after graduating from lectures and the challenges and developments of the era that influenced learning styles and educational interactions. So the solution offered is the accompaniment of Pedagogic Literacy Movement for the characteristics of learners. Method of implementation of socialization, training, self-evaluation, reflective pedagogical paradigm, exploration, simulation, documentation, discussion of friendship, mapping and practice. Objectives Outcome targets: (a) Training and advisory services of knowledge up to the formation of pedagogic competence, (b) Products: Modules, Worksheets, PPR matrices, Journal of Friendship, Matrix Johari Window and TSM, (c) HaKI, (d) Journal of Abdimas Esa Unggul University and additional procedural of SNIPMD, (e) Publication on Esa Superior University repository. The result obtained is an increase in pedagogic literacy. The conclusion is that there are improvements: (a) School paradigm as a learning organization, (b) pedagogic theory knowledge, (c) variation of teaching approach, (d) variation of teaching style, (e) communication model, (f). Ability to identify the characteristics of students, (g) attitude of entry behavior. Keywords: literacy skills, fishbond diagrams, long-term memory AbstrakSDS Hati Kudus memiliki permasalahan sebagai berikut: (a) Guru kelas 5 kurang kreatif dalam menerapkan metode pembelajaran, (b) Kecenderungan guru kelas 5 untuk melatih siswa menghafal daripada memahami, (c) Guru kelas 5 tidak menggunakan tools belajar guna membantu meningkatkan kemampuan pemahaman yang berpengaruh kepada memori jangka panjang, (d) Siswa kelas 5 kurang mendapatkan kesempatan belajar memahami, (e) Belajar banyak terarah kepada konsep menghafal, (f) Penanaman kepercayaan diri belum optimal dan (g) Kurang kesempatan siswa kelas 5 untuk mengemukakan pemahamannya lewat sharing ataupun presentasi. Maka solusi yang ditawarkan: (a) Tahap 1. Pemetaan modalitas belajar siswa, (b) Tahap 2. Tahap memperkenalkan cara belajar memahami melalui penggunaan Fish bond diagram dengan kalimat eksplorasi 5W 1 H, (c) Tahap 3. Tahap bimbingan belajar memahami dengan menggunakan tools fish bond diagram dan pertanyaan eksplorasi 5W 1 H, (d) Tahap 4. Tahap memaparkan dan menjelaskan pemahaman melalui karya, dan (e) Tahap 5. Pengukuran dan Evaluasi Progra. Metode pelaksanaan adalah sosialisasi, pelatihan, evaluasi diri, paradigma pedagogik reflektif, eksplorasi, simulasi, dokumentasi, diskusi pertemanan, pemetaan dan praktek. Hasil yang diperoleh adalah: peningkatan kemampuan literasi dapat meningkat secara efektif dengan penggunaan Fishbond diagram. Kata kunci: kemampuan literasi, fishbond diagram, memori jangka panjang